Evidence of an enhanced near-surface ozone layer at tropical latitudes on Mars - Daniel Viúdez-Moreiras; Michael D. Smith; Mike Wolff; Megan A. J. Brown; Frank Daerden; María-Paz Zorzano; Víctor Apestigue; Ignacio Arruego; Elisa García; Juan J. Jiménez; Daniel Toledo; Mark T. Lemmon; et al. (Proceedings of the National Academy of Sciences, 2025)
Ozone plays a key role in both atmospheric and near-surface chemistry, as well as in UV absorption in planetary atmospheres. Here, we report observations of ozone from the surface of another planet, using the ozone detector included in the Mars Environmental Dynamics Analyzer (MEDA) Radiation and Dust Sensor (RDS) aboard NASA’s Mars 2020 mission, complementing previous space-based and ground-based observations from Earth. Measurements were acquired at Jezero Crater, Mars, at midday, retrieving an average ozone column abundance of 3.8 ± 2.3 μm-atm (1σ) around aphelion, which fell below uncertainties in northern summer. The retrieved column abundance is in reasonable agreement with previous space-based and ground-based observations from Earth. The measurements of total ozone column abundance around aphelion from Mars 2020 and other missions, together with vertical profile observations from orbit, indicate that ~90% of the observed ozone is confined below 20 km of altitude, the aphelion layer weakly contributing to the total column abundance. These ozone levels below 20 km are 3 to 4 times higher than those predicted by models, challenging current understanding of atmospheric chemistry and composition in the lower atmosphere of Mars. It may be possible that aerosols are reducing the destruction pathways of ozone and/or that unknown active chemistry in the near-surface atmosphere of Mars is at work. Both cases should strongly modify the oxidizing capacity in the lower atmosphere of Mars from current model predictions.